أثر الإفصاح المحاسبي على الرقابة المالية في المصارف التجارية: دراسة تطبيقية على مصرف الجمهورية فرع ودان و هون - هناء الدويني المهدي الشيخ (Surman Journal of Science and Technology, 2024)
The Impact of Accounting Disclosure on Financial Control in Commercial Banks (An Applied Study on Jumhouria Bank, Waddan and Hun Branches) This study aims to analyze the impact of accounting disclosure quality on the effectiveness of financial control in commercial banks. It evaluates the extent of compliance with international accounting standards, explores the relationship between transparent disclosure and financial control capabilities, and provides recommendations for improving accounting and control systems. Data were collected through a questionnaire directed at 46 participants and analyzed using SPSS software. The findings revealed: Quality of Accounting Disclosure: Participants expressed satisfaction with accounting disclosure, describing the information as clear, transparent, and useful for decision-making. Level of Transparency: Transparency was deemed essential by participants for building trust and credibility. Financial Control: Participants expressed satisfaction with the bank’s financial control system, highlighting the effectiveness of control policies in promoting stability and protecting rights. Relationship Between Disclosure and Control: Regression analysis indicated a positive and statistically significant relationship between the quality of accounting disclosure and the effectiveness of financial control, with a moderate impact suggesting the influence of other factors. Key Recommendations: Enhancing transparency in financial operations. Developing financial control systems and performance measurement indicators. Providing training programs for employees on disclosure and financial control. Conducting additional studies to identify other factors influencing financial control. The study concluded that the quality of accounting disclosure contributes to improving the effectiveness of financial control, emphasizing the need to enhance transparency and develop control systems in banks.